2014
DOI: 10.1074/jbc.m114.548305
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Phosphoprotein 3 Mediates the Golgi Localization and Function of Protein O-Linked Mannose β-1,2-N-Acetlyglucosaminyltransferase 1

Abstract: Background:The role of GOLPH3 in mammalian glycosylation is not well studied. Results: GOLPH3 binds to and controls the Golgi localization of POMGnT1. Conclusion: GOLPH3 regulates the glycosylation of ␣-dystroglycan by anchoring POMGnT1 at the Golgi. Significance: The result provides a further understanding of the role of GOLPH3 in mediating the Golgi localization of glycosyltransferases in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…There are no direct interactions between the stem and catalytic domains; however, both domains contact the linker region: The interaction areas are 513.6 Å 2 for the stem domain and 925.7 Å 2 for the catalytic domain. Recently, Song's group (22) found that mislocalization of POMGnT1 to the ER occurred in clinically relevant mutations of POMGnT1: E223K, R265H, and C269Y. Our data show that all three residues are involved in the intraprotein interaction as described above.…”
Section: Resultssupporting
confidence: 58%
“…There are no direct interactions between the stem and catalytic domains; however, both domains contact the linker region: The interaction areas are 513.6 Å 2 for the stem domain and 925.7 Å 2 for the catalytic domain. Recently, Song's group (22) found that mislocalization of POMGnT1 to the ER occurred in clinically relevant mutations of POMGnT1: E223K, R265H, and C269Y. Our data show that all three residues are involved in the intraprotein interaction as described above.…”
Section: Resultssupporting
confidence: 58%
“…It is reported that GOLPH3 interacts with and mediates the golgi localization of POMGnT1 [42], a mammalian glycosyltransferase, which promotes glioblastoma progression [43]. In addition, GOLPH3 plays an important role in integrin-mediated cell migration via the up-regulation of sialylation [8], which suggests that GOLPH3 might regulate the progression of the tumors through its biological roles of glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the work of Isaji et al (42), published while our manuscript was under revision. Additionally, a recent article identified LXLRR as a putative motif for GOLPH3 recognition (27). Further work will thus be needed to define the precise consensus sequence of the GOLPH3 binding site to get a better estimation FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GOLPH3 is linked to tumor aggressiveness and poor prognosis in several human cancers (18 -25). Recent studies highlighted an interaction between GOLPH3 and coatomer (11), as well as with the cytosolic tail of the core 2 N-acetylglucosaminyltransferase 1 (C2GnT) (26) and protein O-linked mannose-1,2-Nacetlyglucosaminyltransferase 1 (27). However, evidence for a function of GOLPH3 in COPI-mediated trafficking is still missing.…”
mentioning
confidence: 99%